Effect of Wet Cupping Therapy on reducing blood pressure in primary hypertensive patients: A preliminary study - Ali M. Hassan *; Sarah M. Mohammed Kamel; Ahmed Torad; Amgad Hazzaa; Ahmed M. Salama (SVU - International Journal of Medical Sciences, 2023)
Background: It was reported in the literature that aerobic exercise reduces blood pressure in patients with hypertension. Cupping therapy may be beneficial in reducing hypertension; however, there is a paucity of available literature showing scientific evidence about that. Objectives: Current study aimed to investigate the effect of Wet Cupping Therapy on systolic and diastolic blood pressure in hypertensive Patients Patients and methods: Sixty patients (30 Males and 30 Females) suffering from primary hypertension (46.3± 4.2 years) participated in the study and were randomly divided into two equal groups; the control group received only aerobic exercises [30 min of walking and jogging, with an intensity of 60%-80% of maximal heart rate (Max HR)] for 3 months (3 sessions/week), and the treatment group received the same aerobic exercises as the control group in addition to wet cupping therapy once per month. The current study started in September 2021 till May 2022.The participants’ demographic characteristics were analyzed using t-test and Chi-square test. Within-group differences were investigated using paired t-test while between groups comparisons were investigated using independent t-test. The statistical significance level was set at P ˂0.05. Results: The treatment group showed a statistically significant reduction in blood pressure. Significant differences were noted between groups in favor of the treatment group in the systolic and diastolic blood pressure. Conclusion: Wet cupping therapy combined with aerobic exercises could lead to a significant reduction in blood pressure in primary hypertensive patients.